INSURANCE IN AGRICULTURE - Počuča, Milan; Petrović, Zdravko; Mrkšić, Dragan (Economics of Agriculture, 2018)
Damage in agricultural production can be crucial for the economy of a state, especially in countries where agricultural production prevails in the gross national income, as it is the case with Serbia. However, it is equally important that our agricultural producers manage incomes and expenditures in an efficient manner and optimize profit per surface unit, which is the basis of their business. Insurance plays an important part in the protection of the income statement of every agricultural producer as insurance costs are at the level of 1.5% to 2% on average of the production value, i.e. they are very low and saving on insurance could lead to the loss of the total yield and consequently total profit. However, agricultural insurance in Serbia is not developed enough. The states attempt to boost insurance development amounts to insurance subsidies, which, in the period of the implementation of this regulation, i.e. since 2006, has raised awareness of the need of such a type of protection of agricultural producers.